Effect of head size and rotation on taper corrosion in a hip simulator. (2021) - Wight, C. M.; Whyne, C. M.; Bogoch, E. R.; Zdero, R.; Chapman, R. M.; Citters, D. W. van; Walsh, W. R.; Schemitsch, E.
No abstract available